Arguments to Apply Constitutional Guarantees in the Private Sector - Islam, Md. Toriqul (Lentera Hukum, 2021)
Constitutional guarantees are such a body of interests or basic human rights which are inevitable for each human being. These rights are principally inherent, inalienable, and universal, and therefore, irrespective of race, sex, caste, color, or religion, everyone can enjoy them. Constitutional guarantees are distinct from all other rights and privileges because of at least two unique characteristics, such as intrinsic in nature, and inalienability. These guarantees are crucial in the state-individual relations, and recognized by major laws of the civilized nations, and often enshrined in the national constitutions. For instance, the US Constitution signifies the essence of these rights through the expression of life, liberty, and the pursuit of happiness. Nonetheless, very often, many citizens across the globe are deprived of these rights on numerous pretends and grounds, and mostly, on the public-private dichotomy. This study examined contemporary legal and philosophical discourses as to whether the constitutional guarantees of human rights apply in the private sectors in Malaysia, India, and the United States. This study used doctrinal legal research methodology with a qualitative approach based on library resources. The findings of this study showed that constitutional guarantees, primarily human rights, are presumed to have been neither created nor made but originated like organic growth. Accordingly, no authority can take them away. By examining various logics from theological to socio-historical points of view and the theory of international law, this study concluded that constitutional guarantees, particularly the equal protection of the law, should apply horizontally to cover both public and private sectors. KEYWORDS: Constitutional Guarantees, Human Rights, Public-Private Sectors.